2007
DOI: 10.11606/issn.2176-7262.v40i4p518-530
|View full text |Cite
|
Sign up to set email alerts
|

Abordagem Geral Trauma Abdominal

Abstract: RESUMO:O trauma abdominal é freqüentemente encontrado em situações de emergência. A falta de história adequada do mecanismo de trauma e a presença de lesões que podem ter dor irradiada para o abdome ou a alteração do estado mental, devido a trauma cranioencefálico ou intoxicação por drogas depressoras do sistema nervoso central, podem dificultar o diagnóstico e o tratamento do trauma abdominal. Os pacientes que são vítimas de trauma, freqüentemente, têm lesões intra e extra-abdominais associadas.Este artigo de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
7
0
8

Year Published

2013
2013
2019
2019

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 25 publications
0
7
0
8
Order By: Relevance
“…Most kidney damage (80-90%) occur by closed traumas, usually resulting from traffic accidents involving cars, pedestrians and especially motorcycles 1,4,16 . In our study, the closed mechanism involving traffic accidents especially with motorcycles was also the most common, found in 60.5% of cases, lower values than those referenced in other regions 2,3,7,12 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Most kidney damage (80-90%) occur by closed traumas, usually resulting from traffic accidents involving cars, pedestrians and especially motorcycles 1,4,16 . In our study, the closed mechanism involving traffic accidents especially with motorcycles was also the most common, found in 60.5% of cases, lower values than those referenced in other regions 2,3,7,12 .…”
Section: Discussionmentioning
confidence: 99%
“…The higher the degree of injury, the greater the chance of need for surgical intervention. Overall, injury grades 1 and 2, the most common, are managed conservatively, while larger lesions require a surgical procedure 1 . In our study, the profile of these lesions is different from that found in other studies.…”
Section: Discussionmentioning
confidence: 99%
“…Trauma is a public health problem of great magnitude in Brazil. It is one of the leading causes of death today, due to the increase in urban violence and the technological advancement of the automotive industry, which enabled the production of increased power vehicles 1,2 .…”
Section: Introduction Introduction Introduction Introduction Introducmentioning
confidence: 99%
“…The injuries caused in penetrating abdominal trauma normally affect the liver (40%), small intestine (30%), the diaphragm (20%) and colon (15%). As for the injuries caused by firearm projectiles, they typically affect the small intestine (50%), colon (40%), liver (30%) and abdominal vessels (25%) 1,4 .…”
Section: Introduction Introduction Introduction Introduction Introducmentioning
confidence: 99%
“…Apesar de os exames radiográficos indicarem a presença de corpos estranhos abdominais, eles não identificam precisamente a localização, ou seja, se estão alojados em posição intra ou extraluminal (PEREIRA JÚNIOR et al, 2007). No paciente do presente estudo, apesar de não permitir a localização exata do pino de Steinmann, o exame radiográfico proporcionou a identificação deste, indicando a necessidade de sua remoção imediata, pois havia risco de perfuração de alguma víscera abdominal, uma vez que o pino tinha uma das pontas perfurante.…”
unclassified